Blueprint for clean industry: conclusions and recommendations of the ESID Ministerial Conference (UNIDO ViennaAT, 1993)
Includes general considerations; industry initiatives, government initiatives and international co-operation in achieving ecologically sustainable industrial development (ESID); and future activities of UNIDO.
DC